Coherent EUV lithography with table-top laser - Urbanski, Lukasz, author; Marconi, Mario C., advisor; Bartels, Randy A., committee member; Menoni, Carmen S., committee member; Putkaradze, Vakhtang, committee member (Colorado State University. Libraries, 2012)
This dissertation describes alternative techniques of optical lithography in the extreme ultraviolet (EUV) region of the electromagnetic spectrum. The pursuit of the Moore's law forces the semiconductor industry to transfer to shorter wavelengths of illumination in projection lithography. The EUV light is perhaps the most viable candidate for the next generation integrated circuits printing. However, the EUV lithography encounters many challenges associated with the very nature of the light it is using. Many novel techniques and materials are being applied at the same time in the lithography process. As such the process itself is far from being reliable. Thus the solutions are being sought among the alternative methods of printing in the nano-scale that would aid to temporarily overpass the resolution gap. This thesis contains a description of several alternative techniques of nanofabrication with the EUV light. For each method the analytical description is provided that is further corroborated with numerical model simulations. Furthermore every technique presented here is verified experimentally. The proposed techniques are discussed in terms of their applicability as a self consistent nanofabrication process. The illumination source for all the techniques presented is the capillary discharge laser (CDL) that was engineered at Colorado State University; it is characterized in the chapter 2 of this dissertation. The CDL is an unbeatable table-top source of high average power illumination with the degree of coherence that is sufficient for coherent nano-scale printing. A separate chapter is dedicated to the description of the fabrication protocol of a diffractive optical element (the mask) used in the EUV nanopatterning techniques. This particular chapter is intended to serve as a potential reference manual for the EUV masks fabrication. The coherent EUV nanofabrication techniques described in the chapters 4-6 are: the holographic projection lithography, generalized Talbot imaging (GTI), and de-magnified generalized Talbot imaging. A separate chapter is devoted to the defect tolerance property of the GTI technique.